Akuntabilitas dan Transparansi Pelayanan Publik dalam Perspektif Masyarakat pada Kependudukan dan Pencatatan Sipil Daerah - Fachruddin, Sutiyana; Asriani, Asriani; Ode Rosmina, Wa (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2023)
This study aims to identify and find accountability and transparency in the Services for Making Identity Cards, Family Cards and Birth Certificates at the Department of Population and Civil Registry of the local government of Kendari City in a public perspective related to: 1) Program Accountability and 2) Service information transparency. The research location is at the Kendari City Population and Civil Registry Service Office. The subjects and informants of this study were selected according to the criteria of the people who took care of identity cards (KTP), family cards (KK) and birth certificates at the Department of Population and Civil Registry with as many as 30 residents and employees at related agencies. The informants for this study were determined to be 7 people. The technique for determining informants was based on purposive sampling. Data collection techniques used (1) interviews, (2) observation, (3) questionnaires and (4) literature search. Data analysis techniques using descriptive qualitative According to Hamidi in Susanto (2006: 142) qualitative research data analysis was carried out from the beginning going down to the location to collect data, by "installing or saving" information, reducing, grouping and so on until finally giving interpretation. The results of the study show that there is accountability for public services that have been carried out, namely first, program accountability, which is related to the capabilities and skills of employees. second, Public Accountability, namely clarity of information and service standards for identity cards, family cards and birth certificates, especially in terms of the speed and accuracy of transparent information in serving the public. Transparency in public services has dimensions or actual conditions in public services in improving their services to the community. Certainty regarding the details of service costs must be informed to the public.